Research on Domestic Tourists' Satisfaction When Visiting Tourist Attractions in the Red River Delta - Toai, Doan Ba (Journal of Posthumanism, 2025)
The study aims to identify the factors that directly influence the satisfaction of domestic tourists visiting tourist destinations in the Red River Delta region. Based on 475 survey samples, quantitative analysis methods were employed, including reliability testing using Cronbach’s Alpha, exploratory factor analysis, correlation analysis, and linear regression conducted with SPSS 26 software. The results indicate that eight factors have a direct impact on domestic tourists’ satisfaction when visiting tourist sites in the Red River Delta: Local Characteristics, Trust, Service Capacity, Price, Responsiveness, Tangibles, Security-Safety, and Empathy. Based on these findings, several managerial implications are proposed to help improve the quality of domestic tourism experiences while simultaneously promoting tourism development in a more professional, sustainable, and closely aligned manner with tourists’ actual needs.